Pseudo-healthy image synthesis for white matter lesion segmentation - Bowles, Christopher; Qin, Chen; Ledig, Christian; Guerrero, Ricardo; Gunn, Roger; Hammers, Alexander; Sakka, Eleni; Dickie, David Alexander; Hernandez, Maria Valdes; Royle, Natalie; Wardlaw, Joanna; Rhodius-Meester, Hanneke; et al. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2016)
White matter hyperintensities (WMH) seen on FLAIR images are established as a key indicator of Vascular Dementia (VD) and other pathologies.We propose a novel modality transformation technique to generate a subject-specific pathology-free synthetic FLAIR image from a T1 -weighted image. WMH are then accurately segmented by comparing this synthesized FLAIR image to the actually acquired FLAIR image. We term this method Pseudo-Healthy Image Synthesis (PHI-Syn). The method is evaluated on data from 42 stroke patients where we compare its performance to two commonly used methods from the Lesion Segmentation Toolbox. We show that the proposed method achieves superior performance for a number of metrics. Finally, we show that the features extracted from the WMH segmentations can be used to predict a Fazekas lesion score that supports the identification of VD in a dataset of 468 dementia patients. In this application the automatically calculated features perform comparably to clinically derived Fazekas scores.
CRIS-Team Scopus Importer:2023-03-08